Anti‐phospholipid antibodies are elevated and functionally active in chronic rhinosinusitis with nasal polyps. Issue 8 (14th March 2022) - Eide, Jacob G.; Wu, Jeffanie; Stevens, Whitney W.; Bai, Junqin; Hou, Songwang; Huang, Julia H.; Rosenberg, Jacob; Utz, Paul; Shintani‐Smith, Stephanie; Conley, David B.; Welch, Kevin C.; Kern, Robert C.; et al.
Abstract: Background: Polyps from patients with chronic rhinosinusitis with nasal polyps (CRSwNP) contain increased levels of autoreactive antibodies, B cells and fibrin deposition. Anti‐phospholipid antibodies (APA) are autoantibodies known to cause thrombosis but have not been implicated in chronic rhinosinusitis (CRS). Objective: To compare APA levels (anti‐cardiolipin, anti‐phosphatidylethanolamine (anti‐PE), and anti‐β2 ‐glycoprotein (anti‐B2GP)) in nasal polyp (NP) tissue with tissue from control and CRS without nasal polyp (CRSsNP) patients, we tested whether NP antibodies affect coagulation, and correlate APAs with anti‐dsDNA IgG and markers of coagulation. Methods: Patient specimens were assayed for APA IgG, anti‐dsDNA IgG and thrombin‐anti‐thrombin (TaT) complex by ELISA. Antibodies from a subset of specimens were tested for modified activated partial thromboplastin time (aPTT) measured on an optical‐mechanical coagulometer. Results: Anti‐cardiolipin IgG in NP was 5‐fold higher than control tissue ( p  < .0001). NP antibodies prolonged aPTT compared to control tissue antibodies at 400 µg/mL (36.7 s vs. 33.8 s, p  = .024) and 600 µg/mL (40.9 s vs. 34.7 s, p  = .0037). Anti‐PE IgG antibodies were increased in NP ( p  = .027), but anti‐B2GP IgG was not significantly higher ( p  = .084). All APAs correlated with anti‐dsDNA IgG levels, which were also elevated ( R  = .77, .71 and .54, respectively, for anti‐cardiolipin, anti‐PE, and anti‐B2GP; all p  < .001), but only anti‐cardiolipin ( R  = .50, p  = .0185) and anti‐PE ( R  = 0.45, p  = .037) correlated with TaT complex levels. Conclusions: APA IgG antibodies are increased in NP and correlate with autoreactive tissue antibodies. NP antibodies have in vitro anti‐coagulant activity similar to those observed in anti‐phospholipid syndrome, suggesting that they may have pro‐coagulant effects in polyp tissue. Abstract : In this study, anti‐phospholipid antibodies were found to be increased in nasal polyp tissue and polyp‐derived antibodies affected coagulation similar to those from patients with antiphospholipid syndrome. Tissue antibodies autoreactivity to phospholipids may increase the fibrin deposition that forms the matrix of a nasal polyp.